CONTRASTING PARADIGMS: BETWEEN CAPRA’S ECO-LITERACY AND MULYADHI’S TRILOGY IN ADDRESSING THE ECOLOGICAL CRISIS - Tanzila Feby Nur Aini; Suwendi (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2024)
This research explores the philosophical views of Fritjof Capra and Mulyadhi Kartanegara regarding nature, aiming to shift the anthropocentric reasoning of modern humans. The dominance of Western thought in the modern world, characterized by rationalism, materialism, and empiricism, has led to a lack of spiritual awareness. This mechanistic paradigm causes modern humans to perceive nature as a mere object, operating like a machine without spirituality, thus reducing it to an instrument for human exploitation. Consequently, this perspective fosters exploitative behaviors that contribute to the ongoing ecological crisis. To address this issue, Capra and Kartanegara propose new paradigms that prioritize not only human interests but also the well-being of the universe as a whole. Although they employ different approaches, both thinkers offer alternative paradigms emphasizing the unity of nature, respect for living beings, and human responsibility in maintaining ecological balance. Capra bases his views on modern science and ecology from a holistic perspective, while Kartanegara draws from Islamic theology and classical philosophy. This research is based on a literature study that examines the writings of both scholars alongside relevant secondary sources.